La question du silence dans les discours critiques sur les représentations de la Shoah - Luba Jurgenson (Çédille: Revista de Estudios Franceses, 2015)
The reflexion on the Shoah is inseparable from the question of silence. This is due to the event itself, which carries with it the project of the complete disappearance of murdered Jews and erasure of their traces. This is due also to the place this issue occupies in western thought. In the second half of the 20th century an important dimension of western and especially French thought is founded on the overturning that the Shoah has caused in the European culture and the European self-representation. The author proposes to examine – through some philosophical and literary examples – the paradigm of the erasure of the subject in France, in relation to the genocide.